Non-Conventional Hybrid Machining Processes Theory and Practice - Singh, Rupinder 1979-; Davim, J. Paulo 1964- (CRC Press, Taylor & Francis Group, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Editors -- Contributors -- Chapter 1 Ultrasonic Vibration-Assisted Sintering -- 1.1 Introduction -- 1.1.1 Ultrasonic -- 1.1.2 Sintering -- 1.2 Literature Based on Ultrasonic-Assisted Sintering -- 1.3 Horn Design for UAS -- 1.4 Working Principle -- 1.5 Important Processing Parameters -- 1.5.1 Ultrasonic Power -- 1.5.2 Ultrasonic Time -- 1.5.3 Sintering Parameters -- 1.5.4 Pressure -- 1.5.5 Powder Size and Shape -- 1.6 Effect on Microstructure -- 1.7 Advantages, Case Study, Challenges, and Future Scope -- 1.7.1 Advantages -- 1.7.2 Case Study -- 1.7.3 Challenges and Future Scope -- 1.8 Summary -- References -- Chapter 2 Hybrid EDM with Three-Phase Dielectric Medium -- 2.1 Introduction -- 2.1.1 Electrical Discharge Machine (EDM) -- 2.1.2 Hybrid EDM with Three-Phase Dielectric Medium -- 2.2 Experimental Procedures -- 2.2.1 Experimental Setup -- 2.2.2 Materials -- 2.2.3 Measuring Equipment -- 2.3 Design of Experiment (DOE) -- 2.3.1 DOE for Comparing the Surface Texture -- 2.3.2 Taguchi Method -- 2.4 Results and Discussion -- 2.4.1 Comparison of the Surface Texture of EDM Processes -- 2.4.2 Optimization of Processing Parameters -- 2.4.3 Confirmation Test -- 2.5 Conclusions and Scope for Future Work -- Acknowledgment -- References -- Chapter 3 Fabrication of Microchannels using Conventional and Hybrid Machining Processes -- 3.1 Introduction -- 3.2 Conventional Methods -- 3.2.1 Lithography -- 3.2.2 Wet and Dry Etching -- 3.2.3 Laser-Evolved Microchanneling -- 3.2.4 Powder Blasting -- 3.3 Hybrid Machining Processes -- 3.3.1 Electrochemical Discharge Machining (ECDM) -- 3.3.2 Ultrasonic-Assisted Hybrid Machining -- 3.4 Case Studies -- 3.5 Conclusion -- References -- Chapter 4 Modified Ultrasonic Machining Process -- 4.1 Introduction
Keywords: Machining; Spanende Bearbeitung; Hybridtechnik